Model Blended Learning Dengan Menerapkan Experiential Learning - Diana Ariani (Universitas Negeri Jakarta, 2018)
This article describes the Blended Learning training model specifically developed by Experience Learning. The model in question is the APKL model, and the model is designed to develop compound learning through the use of experimental learning. APKL itself stands for